Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.4081/ejh.2021.3352
|View full text |Cite
|
Sign up to set email alerts
|

Different fusion tags affect the activity of ubiquitin overexpression on spastin protein stability

Abstract: Spastin is one of the proteins which lead to hereditary spastic paraplegia (HSP), whose dysfunction towards microtubule severing and membrane transporting is critically important. The present study is to elucidate the mechanisms of the protein stability regulation of spastin. The ubiquitin encoding plasmids are transfected into COS-7 cells with different fusion tags including Green Fluorescent Protein (GFP), mCherry and Flag. The expression level of spastin was detected, microtubule severing activity and neuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“… 29 , 30 Spastin is highly expressed during development and promotes axon elongation by severing long microtubules to short segments. 18 When the expression of spastin is disturbed, significant defects can occur in the delivery of presynaptic vesicles and postsynaptic α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors. 31 Spastin promotes microtubule amplification by increasing the rate at which shrinking microtubules are converted into growing ones (called rescue) so that the microtubule fragments created by severing act as seeds for the growth of new microtubules.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 29 , 30 Spastin is highly expressed during development and promotes axon elongation by severing long microtubules to short segments. 18 When the expression of spastin is disturbed, significant defects can occur in the delivery of presynaptic vesicles and postsynaptic α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors. 31 Spastin promotes microtubule amplification by increasing the rate at which shrinking microtubules are converted into growing ones (called rescue) so that the microtubule fragments created by severing act as seeds for the growth of new microtubules.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of microtubule severing proteins, such as spastin or katanin, within COS7 cells and staining of microtubules are currently commonly used to quantify microtubule severing activity, as previously reported. 18,24 The results showed that compared to the fluorescence intensity of microtubules in COS7 cells in the GFP vector control group, both GFP-spastin WT and GFPspastin 11A significantly reduced the fluorescence intensity of microtubules (Figure 3 A,B). Interestingly, the difference between the GFP-spastin 11A group and the GFP-spastin WT group was not statistically significant (p>0.05) (Figure 3B).…”
Section: Genementioning
confidence: 94%
See 1 more Smart Citation